(untitled) (Collection of scientific works «Modern structures of metal and wood», 2023)
The article presents the results of theoretical studies on embodied carbon for load- bearing wall structures prevailing in low-rise buildings consturction practice in order to reveal the potential of timber structures in decarbonization of the construction sector. Seven types of wall structures were considered in the study. CO 2 emissions were determined using the environmental product declarations for relevant materials considering sequential life-cycle stages (raw material supply, production and transportation of building products, construction process, building waste transportation and disposal) with regard to recycling benefits. A lightweight timber framed wall panel was shown to have minimum carbon emissions at each life-cycle stage leading to lowest total carbon embodied.